Impacts of Saudi-Israel Relations on the Middle East: An Analysis - Dr. Zahid Yaseen; Dr. Muhammad Muzaffar; Kinza Tariq (Journal of Political Studies, 2023)
This qualitative study aims to analyze the impact of Saudi-Israel relations on the Middle East. The study also focused on the reaction of Arab countries to their bilateral ties and incidents that have arisen in the Middle East as a direct result of tensions between Saudi Arabia and Israel. The deteriorating condition of relations between Israel and Saudi Arabia wreaked havoc throughout the region. The United States plays a pivotal role in the politics of the Middle East; therefore, a nation that is willing to operate as the United States' right hand was sorely needed in the region. Israel, a country that is not recognized on a global scale, has set up shop in that vacated seat. Together, they aid proxy wars between Saudi Arabia and Iran, which contributes to instability in the region. The only thing that could diminish the damage would be a concerted effort by Muslim states against Israel